Outcome of Corticosteroid Injections, Extracorporeal Shock Wave Therapy, and Radiofrequency Thermal Lesioning for Chronic Plantar Fasciitis - Erden, Tunay; Toker, Berkin; Cengiz, Omer; İNCE, Buğra; İNCE, BUĞRA; Asci, Seyda; TOPRAK, ALİ; TOPRAK, ALİ (My University, 2020)
Background: Chronic heel pain with plantar fasciitis is relatively common and can affect adults of all ages regardless of an active or sedentary lifestyle. The purpose of the present study was to evaluate the effectiveness of corticosteroid injection (CSI), extracorporeal shock wave therapy (ESWT), and radiofrequency thermal lesioning (RTL) treatments in chronic plantar heel pain that has been unresponsive to other conservative treatments. Methods: We retrospectively analyzed the results of 217 patients treated with CSI (n= 73), ESWT (n= 75), and RTL (n= 69). The treatment efficacy and pain intensity, as measured using the visual analog scale, were recorded and compared at the 6-month follow-up. Results: Pain intensity decreased significantly in all patients. However, it decreased significantly more in the CSI and RTL groups than in the ESWT group (P .05). No complications were noted after the CSI, ESWT, or RTL sessions. Conclusion: CSI, ESWT, and RTL successfully treated chronic plantar heel pain that did not respond to other conservative treatments; however, CSI and RTL yielded better therapeutic outcomes.